RHETORICAL MOVES IN THE BACKGROUND SECTIONS OF EFL INDONESIAN VOCATIONAL COLLEGE STUDENTS - Rahayu, Titik; Permatasari, Ita; Mudofir, Imam; Sutantohadi, Alief; Maftuh, Moh. Farid (LLT Journal: A Journal on Language and Language Teaching, 2022)
Rhetorical moves in academic writing are interesting topics and strategic issues in linguistics. Many studies have investigated the moves in all sections of research articles for example abstract, introduction, research method, findings and discussion, and conclusion. However, few studies investigated the rhetorical moves found in vocational college students’ academic writing, particularly in a background section. Therefore, this current research was aimed at revealing the rhetorical moves and patterns in the background of the study. This study analyzed 29 background sections from final project reports of vocational college students enrolled in the English study program of one of the state polytechnics in Indonesia. The reports were developed based on two major areas namely tourism and journalism. The data were analyzed by referring to the CARS model by Swales (2004). This research revealed that Move 1 and Move 3 occurred in all background sections. However, Move 2 was not used in several background sections although Step 1 in Move 2 is obligatory. Regarding the rhetorical patterns, seven patterns were found with different frequencies. The most used pattern was M1-M3S1. The current study may give implications to pedagogical settings related to the emphasis on establishing a niche in the background section.